Promotion and Price Analysis on Member Loyalty - Fatimah Nur Syah Alam; Desy Oktaviani (International Journal of Economics Development Research (IJEDR), 2023)
This study aimed to determine how much promotional activities and pricing strategies influence membership loyalty at Galby Gym Citeureup. This study uses a quantitative research methodology. The methodology used for data collection involved distributing questionnaires with a sample size of 65 participants. The sampling methodology used requires probability sampling techniques, with particular emphasis on simple random sampling. The data processing methodology used in this study is the use of SPSS version 25 software designed for the Windows operating system. The results of this study prove that there is an influence of promotion on membership loyalty of Galby Gym Citeureup. Price has a positive effect on Galby Gym Citeureup membership loyalty. As well as, promotions and prices have a positive effect on membership loyalty of Galby Gym Citeureup.